Write "f(x)*g(x) =" followed by the first function in parentheses, a multiplication symbol, then the second function in parentheses.
Example:
f(x) = x - 2
g(x) = x^2 + 2x + 3
f(x)*g(x) = (x - 2)*(x^2 + 2x + 3)
Use the distributive property to multiply the two functions. If both functions consist of two terms, you have a special case of the distributive property which you may have learned as the FOIL method (first, outside, inside, last). Make sure to multiply each term in the second function by every term in the second function exactly once.
Example:
f(x)*g(x) = (x - 2)*(x^2 + 2x + 3)
f(x)*g(x) = x*x^2 + x*2x + x*3 - 2*x^2 - 2*2x - 2*3
f(x)*g(x) = x^3 + 2x^2 + 3x - 2x^2 - 4x - 6
Combine like terms and order the terms by their exponents in descending order. Recall that "x" with no power is the same as "x^1," and constant terms like "2" are the same as "2*x^0," since x^0 = 1.
Example:
f(x)*g(x) = x^3 + 2x^2 + 3x - 2x^2 - 4x - 6
f(x)*g(x) = x^3 +2x^2 - 2x^2 + 3x - 4x - 6
f(x)*g(x) = x^3 - x - 6